Social and Economic status of Casino women in Nepal - K.C., Raju (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
The research aims to explore the women status in casino job. The research has been performed by the survey, interview and participant observation in their everyday job. Upon examination of this situation, it becomes clear that casino job status is meaningful in Nepalese community which has brought tremendous changes in their life world and that has brought stratification on them. Gender based society like Nepal has more peculiar obstacles effect on women where they faced more difficulties on their daily life. They are suppressed from the social deformities like teasing, touching and other verbal amusement from male on the issue of job in Casino. Using of Teenagers women in casino only for the entertainment mechanism was developed. Aged women are neglected in the job as well. Participation of such a woman in the casino, directly or indirectly help on tourism sector of Nepal. The women labourers of the casino were found enjoyed with facilities provided such as economic, transportation, allowances, medical etc. Since the labourers both male and female work in close proximity, the relationship between the female co-workers and the customers was in good condition. The concerned authorities have not paid due attention to the plight of these simple hard working labourers who has made significant contribution towards increasing gross national product and also earning foreign currency.